TASAWUF SEBAGAI TERAPI PROBLEMATIKA MASYARAKAT MODERN - Lilik Suhartiningsih; Fitri Rahmawati; Ahmad Shofiyul Himami (LP3M IAI Al Urwatul Wutsqo Jombang, 2021)
Today, the glittering worldly sights that at first glance are so very tempting are clearly painted on the canvas of life, crowded with materialistic and hedonistic traits, even today we can easily access everything with just the index finger. A luxurious lifestyle is widely regarded as the capital of happiness and serenity. Sufism is like a cure for disease in an era with all the negative effects that are infected in it, like the froth of dew that soothes the arid minds of people who only call for mortal favors. Sufism is presented by God with all spiritual teachings that form noble character who will play its main role in offering solutions to the problems of modern society which if left unchecked can destroy the nation's future. So to deal with this kind of disease we really need a doctor who is an expert in the field of spirituality and morality. Through the intermediary of this paper, it was found that the values ??contained in Sufism will be a medicine for the diseased soul as above so that it can harmonize life amidst the hustle and bustle of the materialistic world so that good morals can be nurtured with the blessing of Allah SWT.